EKSISTENSI ETNIS TIONGHOA DALAM BIDANG SOSIAL DAN BUDAYA DI INDONESIA TAHUN 1966-2016 - Egie Ferlando; Ragil Agustono (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
Chinese ethnicity is one of the ethnic groups spread all over the world. This means that ethnic Chinese exist in every country and one of them is in Indonesia. It is well known that ethnic Chinese are part of the diversity of the Indonesian nation that existed long before independence, its long journey and its role as ethnic group that participated in Indonesian independence and development did not seem to be a positive value for them in the eyes of other indigenous ethnic groups in Indonesia, at least in some cases of discrimination that had occurred in Dutch colonialism until the famous during the new order government in the period long enough before the birth of government reform in 1998. The purpose of this study is To describe the existence of ethnic Chinese in the social and cultural fields in Indonesia in 1966- 2016. Research Methods in this study using historical research conducted in the library University of Muhammadiyah Metro. In this study the researcher uses the historical method by conducting literature study. Data collection techniques in this study using heuristics step and literatur techniques and the validity of data collection using internal and external critism with the steps of analysis that is using interpretation and historiography.